Inovasi Media Pembelajaran Android Berbasis Construct 2 pada Materi SPLDV untuk Mendukung Pembelajaran Matematika Interaktif - Rezki Ayu Ramadhani; Aliyah Rahmah. D; Muhammad Ilham; Lisnasari Andi Mattoliang; Ahmad Farham Majid (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This research is motivated by students' difficulties in understanding and solving Linear Equation System of Two Variables (SPLDV) problems. This study aims to develop a valid, practical, and effective Android-based learning media using Construct 2 on SPLDV material to support interactive mathematics learning. This research employs a Research and Development (R&D) method, utilizing a 4D model (Define, Design, Develop, and Disseminate). The research subjects were 30 eighth-grade students at MTsN Gowa. The instruments used included validation sheets, teacher and student response questionnaires, as well as pre-test and post-test. The results showed that the learning media met the very valid criteria with an average expert assessment percentage of 94.52%. The media was also declared very practical based on 100% learning implementation, 92.50% teacher response, and 89.56% student response. Furthermore, the media proved effective with a classical completeness of 76.67% and an increase in average student learning outcomes from 27.17 to 80.50. In conclusion, this Android-based learning media is feasible and effectively used as an interactive learning alternative for SPLDV material.